2022
DOI: 10.18240/ijo.2022.10.18
|View full text |Cite
|
Sign up to set email alerts
|

Globe penetration during loco-regional anesthesia: prevalence and review of cases

Abstract: AIM: To describe prevalence and different clinical signs and management of cases with penetrating eye injuries during loco-regional anesthesia for ophthalmic surgery. METHODS: A retrospective review of clinical records was carried out, identifying cases of globe penetration secondary to peribulbar anesthesia injection during 5y activity in Centro de Oftalmología Barraquer. RESULTS: A total of 17 460 needle-based ocular anesthesia procedures were performed in our centre and 4 cases of globe penetration were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 54 publications
(63 reference statements)
0
4
1
Order By: Relevance
“…Gopal et al [23] reported five cases of RD after globe perforation for PBA. Differently from our case, which was hyperopic, all the cases reported were highly myopic eyes with a higher risk of globe perforation due to the scleral staphyloma [4][5][6]13] Gomez-Benlloch et al reported a percentage of 0.024% (4 of 17,460 eyes) [9]. Two of the four cases reported were highly myopic, and two cases developed RD complicated by choroidal detachment.…”
Section: Discussioncontrasting
confidence: 69%
See 4 more Smart Citations
“…Gopal et al [23] reported five cases of RD after globe perforation for PBA. Differently from our case, which was hyperopic, all the cases reported were highly myopic eyes with a higher risk of globe perforation due to the scleral staphyloma [4][5][6]13] Gomez-Benlloch et al reported a percentage of 0.024% (4 of 17,460 eyes) [9]. Two of the four cases reported were highly myopic, and two cases developed RD complicated by choroidal detachment.…”
Section: Discussioncontrasting
confidence: 69%
“…However, our patient had no high-risk factors, and in this case, one possible explanation was that the surgeon applied an incorrect angle of needle insertion. Some features of the administration technique of the anesthetic drugs, such as the use of sharp long needles and the use of multiple injections, have been described as risk factors for ocular penetration [9]. In our case, peribulbar anesthesia with a 25-gauge 25 mm sharp needle was used.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations